Long follow-up of Multiple Recurrent Calcific Masses–A rare case report of Hyperphosphatemic Familial Tumoral Calcinosis - Saad Ahmed; Saeed, Ayesha; Shafique Farooq; Zeeshan Yaqoob; Fatima tul Zohra; Muhammad Waqas (Journal of University Medical & Dental College, 2022)
Hyperphosphatemic familial tumoral calcinosis (HFTC) is an autosomal recessive benign condition of dysregulated phosphate metabolism (biallelic mutation in GLANT3, KLOTHO or FGF23) due to deficiency or resistance of intact fibroblast growth factor 23 resulting in deposition of large amount of ectopic calcium salts in periarticular soft tissues. We present a 21-year male with multiple recurrent masses around both hips, feet, left knee, and left elbow. His serum inorganic phosphate levels and ratio of renal tubular reabsorption rate of phosphate to corrected glomerular filtration rate were markedly elevated. Medical treatment to lower serum phosphate levels by placing him on tablet sevelamer hydrochloride and acetazolamide and surgical excision of the periarticular masses lead to disease remission. At 4 years follow up he has no recurrence and his functional scores (SF 36 and Harris Hip Score) have tremendously improved. Tumoral calcinosis, though rare must be kept in mind as a differential in abnormal calcific masses and with good radiological and laboratory support can be diagnosed early.